Tropical-subtropical south american midsummer precipitation under ENSO events - Hurtado, Santiago Ignacio (2024)
El Niño-Southern Oscillation (ENSO) is the major forcing of interannual precipitation variability over South America (SA), especially from September to December, through a convection dipole over the South Atlantic Convergence Zone (SACZ) region and southeastern SA (SESA). However, the forcing mechanisms for midsummer (January) precipitation under ENSO events is less known. A cluster analysis applied to January OLR anomalies over Tropical-Subtropical SA under ENSO events depicts two clusters linked to the signs of the convection dipole between SACZ region and SESA. Most La Niña (LN) events (10 out of 13 events) are associated with enhanced convection over SESA and inhibited convection over SACZ region in January. El Niño (EN) events show both signs of the convection dipole in equal proportions, evidencing a non-linear response. In January, for EN and LN, enhanced (inhibited) convection over SESA and inhibited (enhanced) convection over SACZ region are associated with anticyclonic (cyclonic) tropospheric circulation over southeast Brazil, as observed in EN (LN) spring. During LN events, lower tropospheric circulation in January depends on the local thermodynamic conditions over central east Brazil in the previous months (Nov-Dec). If there are dry and warm (wet and cold) conditions over central east Brazil in Nov-Dec, a thermal low (high) sets up. In contrast, under EN events if the dry and warm conditions over east Brazil in Nov-Dec are overall weak, an anticyclonic tropospheric circulation is established in southeast Brazil in January due to a predominant large-scale anomalous Walker cell. Lastly, the studied relationship may be used to build and assess sub-seasonal forecasting tools for January precipitation anomalies.